Efficacy of high-dose vs. low-dose vitamin D₃ supplementation in children with chronic tic disorders: a randomized controlled trial - Zakaria Ahmed Mohamed; Miaoshui Bai; Hanyu Dong; Yang Xue; Feiyong Jia; Junyan Feng (Nutrition Journal)
Abstract Background Vitamin D₃ has emerged as a potential therapeutic agent for alleviating tic symptoms in children with chronic tic disorders (CTDs). This study aims to evaluate the comparative efficacy of high-dose and low-dose vitamin D₃ supplementation on tic severity and serum 25-hydroxyvitamin D 25(OH)D levels in children with CTDs. Methods A randomized controlled trial was conducted with 83 children aged 4 to 15 years diagnosed with CTDs. Participants were randomly assigned to receive either high-dose vitamin D₃ (5,000 IU/day) or low-dose vitamin D₃ (1,000 IU/day) for three months. The primary outcome was tic severity, assessed using the Yale Global Tic Severity Scale (YGTSS), while secondary outcomes included changes in serum 25(OH)D and calcium levels. Tic severity and biochemical markers were measured at baseline and after the intervention to assess the effects of vitamin D₃ supplementation. Results Both the high-dose and low-dose groups showed significant improvements in tic severity and increases in serum 25(OH)D levels (𝑝 < 0.05). The high-dose group exhibited a significantly greater reduction in tic severity and a more substantial increase in serum 25(OH)D levels compared to the low-dose group (𝑝 < 0.05). No significant differences were observed in serum calcium levels between the group (𝑝 > 0.05). Furthermore, multivariate linear regression analysis revealed a significant negative association between increases in serum 25(OH)D levels and reductions in tic severity (𝑡 = -2.816, 𝑝 < 0.05). Conclusion High-dose vitamin D₃ supplementation is more effective than low-dose supplementation in reducing tic severity and increasing serum 25(OH)D levels in children with CTDs. These findings suggest that high-dose vitamin D₃ may serve as a valuable adjunctive therapy for managing CTDs.